Development of Microsatellite Markers to Determine Genetic Diversity of Indonesian Betel Nut (Areca catechu L.) - Muhammad Roiyan Romadhon; Sobir; Willy Bayuardi Suwarno; Deden Derajat Matra (Future Science, 2023)
Areca nut (Areca catechu) belongs to the monocotyledonous and palm family of plants known as betel nut or supari plants. The Center of origin areca nut comes from India. Areca nut is a cross-pollinated plant with a heterozygous heterogeneous genetic constitution. Next-generation sequencing is widely used for plant breeding activities, including developing SSR markers with an in-silico approach. This research aims to develop an SSR marker to detect genetic diversity in local areca nut from Indonesia. The genomic data used to develop SSR markers were obtained from the Whole Genome Sequencing of Pinang Reyan Hainan Cultivars obtained from NCBI. Fragments containing SSR regions were isolated using MISA software, and primers were designed with Primer3web v.4.1.0 (https://bioinfo.ut.ee/primer3/). The average total size of the sequences tested was 168770731.8, with a total number of SSRs identified as many as 1149,813. SSR motifs are used as a step in genetic diversity research because these motifs will be used in primary attachments which in turn can affect genetic diversity. There were twenty-eight primers generated from four amplicons (100-150, 150-200, 200-250, and 250-300 bp) used for multiplex primers with motifs (AAT)37, (TA)53, (TA)54, (TC)52, (TC)52, (TG)53, and (AG)54.